Between happiness and reverie. An approach to Meléndez Valdés anacreontic poetry - Pérez Lasheras, Antonio (Tropelías: Review of Literary Theory and Comparative Literature, 1995)
This paper wants to approach to that poetic genre characteristic of the eighteenth century the anacreontics, so many times considered as "minor poetry". But if they are examined in detail, they entail a fundamental element of study for the analysis of the establishment of their author’s philosophical ideas and the better understanding of the evolution of a thinking that is changing constantly. The case of the poet Juan Meléndez Valdés offers to us an extreme possibility for this kind of studies (although here is only outlined) by the knowledge of the progression that the poet wanted to give to his compositions.